2020
DOI: 10.3390/ani10091574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Use of Tomato Pomace on Feeding and Performance of Lactating Goats

Abstract: The aim of this research was to evaluate the effect of including different levels of tomato pomace (TP) on performance, blood biochemical parameters, hormones, production and composition of milk, and economic analysis of Saanen goats reared in confinement. Sixteen multiparous goats (Saanen), 21 days in milk, were randomly distributed in two Latin square 4 × 4 (four periods and four treatments), according to the inclusion levels of dehydrated tomato pomace (0%, 20%, 40%, and 60%) in the diet. This inclusion res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…It had no effect on the ratio of conjugated linoleic acid. Mizael et al [ 18 ] found that feeding different levels of TP to lactating ewes did not affect blood biochemical indicators and thyroid hormones, feed efficiency, or feed conversion ratio, but feeding 60% of the level would reduce the body weight of the ewes. Supplementation by 20% and 40% increased milk quality and fat content, respectively.…”
Section: Nutrition Of Tp On Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It had no effect on the ratio of conjugated linoleic acid. Mizael et al [ 18 ] found that feeding different levels of TP to lactating ewes did not affect blood biochemical indicators and thyroid hormones, feed efficiency, or feed conversion ratio, but feeding 60% of the level would reduce the body weight of the ewes. Supplementation by 20% and 40% increased milk quality and fat content, respectively.…”
Section: Nutrition Of Tp On Ruminantsmentioning
confidence: 99%
“…When the tomato supplementation level was 35%, the final body weight, total weight gain, average daily weight gain, and weed intake increased significantly. Mizael et al [ 18 ] reported that, although the addition of TP to the dairy goat diet had no difference in feed efficiency and feed conversion ratio, it improved milk quality and fat content. Mohammed et al [ 19 ] found that the addition of 4% and 6% TP had no adverse effects on chicken growth performance, meat quality, or hormone secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a circular economy is one of the principles of the European Green Deal that aims to improve the efficiency of resource use and to cut pollution, for instance [16,17]. Recent publications support the potential utilization of this strategy [18][19][20][21][22][23][24]. It is also important to mention that the reutilization of residues of the food industry and the consequent development of food products are concepts supported and well-accepted by consumers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato pomace is a mixture of tomato cuticle (or peel), seeds and small amounts of pulp that remain after processing (Ventura et al, 2009). It is often used in animal feed (Mizael et al, 2020) as a source of dietary fiber, as well as B vitamins, lycopene and to a lesser extent vitamin A, for example, in California (which accounts for 95% of US production) most of the pomace is added to cattle feed for dairy farms. The alternative to use in animal feed is landfilling; this, for instance, represents the prevailing end-of-life route in the US Midwest.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, tomato pomace is either given for free to farmers or is sent to landfill, which represents an added cost of 200 euros per ton for the producing companies. Overall, the use of tomato pomace is limited by the risk of ruminal acidosis caused by pomace acidity (Mizael et al, 2020) or the high moisture content (60-80% wt.) leading to fast spoiling and pollution hazard.…”
Section: Introductionmentioning
confidence: 99%